Analysis of the Implementation of Fixed Asset Accounting Policies based on PMK Nomor 22/PMK.05/2022 Regarding Central Government Accounting Policy at the Regional Office of the Ministry of Religion, North Sulawesi Province - Marcella Vincensia Angela Winokan; Lintje Kalangi; Sherly Pinatik (Formosa Journal of Applied Sciences, 2023)
The purpose of acquiring fixed assets is also different in companies. Fixed assets are used to support company operations in order to gain profits, while in governments, fixed assets are used as the main facilities or infrastructure to support operational activities and provide the best possible service to the community. So that fixed assets used by government agencies need fixed asset accounting treatment. The aim of this research is to analyze the suitability of the implementation of fixed asset accounting policies in the Regional Office of the Ministry of Religion of North Sulawesi Province with Minister of Finance Regulation No. 22/PMK.05/2022 concerning central government accounting policies. The type of research used is descriptive qualitative. The research results showed that the implementation of fixed asset accounting regarding the classification, recognition, measurement and disclosure of fixed assets at the Regional Office of the Ministry of Religion of North Sulawesi Province was in accordance with Minister of Finance Regulation No. 22/PMK.05/2022 has been carried out well.